CCNP security VPN 642-647 quick reference - Matei, Cristian (Cisco Press, 2011)
As a final exam preparation tool, the CCNP Security VPN 642-647 Quick Reference provides a concise review of all objectives on the new CCNP Security VPN exam (642-647). This eBook provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on deploying Cisco ASA-based VPN solutions. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts.